Reduced Anxiety-Like Behavior and Altered Hippocampal Morphology in Female p75NTRexon IV−/− Mice - Puschban, Zoe; Sah, Anupam; Grutsch, Isabella; Singewald, Nicolas; Dechant, Georg (Frontiers in Behavioral Neuroscience, 2016)
The presence of the neurotrophin receptor p75NTR in adult basal forebrain cholinergic neurons, precursor cells in the subventricular cell layer and the subgranular cell layer of the hippocampus has been linked to alterations in learning as well as anxiety- and depression- related behaviors. In contrast to previous studies performed in a p75NTR exonIII-/- model still expressing the short isoform of the p75NTR, we focused on locomotor and anxiety–associated behavior in p75NTR exonIV-/- mice lacking both p75NTR isoforms. Comparing p75NTR exonIV-/- and wildtype mice for both male and female animals showed an anxiolytic-like behavior as evidenced by increased central activities in the open field paradigm and flex field activity system as well as higher numbers of open arm entries in the elevated plus maze test in female p75NTR knockout mice. Morphometrical analyses of dorsal and ventral hippocampus revealed a reduction of width of the dentate gyrus and the granular cell layer in the dorsal but not ventral hippocampus in male and female p75NTR exonIV -/- mice. We conclude that germ-line deletion of p75NTR seems to differentially affect morphometry of dorsal and ventral dentate gyrus and that p75NTR may play a role in anxiety-like behavior, specifically in female mice.